Mismatch : why our world no longer fits our bodies - Gluckman, Peter D. (Oxford University Press, 2006)
We have built a world that no longer fits our bodies. Our genes - selected through our evolution - and the many processes by which our development is tuned within the womb, limit our capacity to adapt to the modern urban lifestyle. There is a mismatch. We are seeing the impact of this mismatch in the explosion of diabetes, heart disease and obesity. But it also has consequences in earlier puberty and old age. Bringing together the latest scientific research in evolutionary biology, development, medicine, anthropology and ecology, Peter Gluckman and Mark Hanson, both leading medical scientists.